ANALISIS JARINGAN PEMASARAN SAYURAN KUBIS DI PASAR SAYUR KARANGPLOSO KABUPATEN MALANG - Wesli, Wesli; Masduki, Said; Arvianti, Eri Yusnita (Universitas Tribhuwana Tunggadewi, 2018)
Karangploso market is an area several vegetables that play a role in meeting the needs of consumers in the cabbage. Cabbage marketing network from farmers to consumers will determine the price of farmers, intermediaries and consumers. This study aims to examine the structure and behavior of the market, knowing cabbage marketing margins, and efficient marketing of cabbage in the vegetable market Karangploso. Data were obtained by direct interview and questionnaire with respondents ie farmers, collecting traders, retailers and consumers of cabbage. The method of analysis used in this research is descriptive quantitative. Quantitative methods use marketing margin and marketing efficiency analysis economically by calculating farmer's share. The results show that, there are three marketing networks, marketing margin shows that the longer the marketing network the higher the operational costs incurred. Pasar Karangploso merupakan pasar yang menjual beberapa jenis sayuran yang berperan dalam memenuhi kebutuhan konsumen di antaranya kubis. Jaringan pemasaran kubis dari petani hingga konsumen akan menentukan besarnya harga di tingkat petani, pedagang perantara dan konsumen. Penelitian ini bertujuan untuk mengkaji struktur dan perilaku pasar, mengetahui marjin pemasaran kubis, dan efisien pemasaran kubis yang ada di pasar sayur Karangploso. Data diperoleh dengan wawancara langsung dan kuesioner dengan responden yaitu petani, pedagang pengumpul, pedagang pengecer dan konsumen kubis. Metode analisis yang digunakan dalam penelitian ini adalah deskriptif kuantitaif. Metode kuantitaf menggunakan analisis marjin pemasaran dan efisiensi pemasaran secara ekonomis dengan menghitung farmer?s share. Hasil penelitian menunjukkan bahwa, terdapat tiga jaringan pemasaran, marjin pemasaran menunjukan bahwa semakin panjang jaringan pemasaran maka semakin tinggi biaya opersional yang dikeluarkan.